Violence in our tertiary institutions the need for psychological intervention: a Nigerian experience (2007)
In this paper the importance of the role culture played and the nature of complexity in its definition by various researchers in social science and anthropology have been explained. Beside this, the society and personality, which are complex inseparable factors in nature, have also been examined. The paper observed that ability to adjust or adapt to the environment played a great role in psychological well being of a person. It was however, noted that apart from the developmental problems, global problems within Nigeria take the greatest share. For instance, university students had not been spared from these psychosocial menace where criminal activities, cultism, violence are prevalent in all our universities and other tertiary institutions. The major factors of interest in the paper are the implication for early identification of students who are prone to engage in such deviant behaviour. With the present standardisation of Logotest (IMF scale) among the University of Ibadan student which has been found to be an appropriate tool for not only deviant behaviour but also the assessment and diagnosis of meaning of life/inner meaning fulfilment and existential problems/neurosis/frustration, it is expected that other colleagues in Africa would look into these aspects and take them into consideration in their respectively territary Institutions and other relevant Institution and Non governmental organisation.